Penerapan Kimia Hijau Dan Pengetahuan Lingkungan Serta Keterkaitannya Dengan Perilaku Peduli Lingkungan - Santosa, Ni Ketut Yuli; Sulistyowati, Lilik; Aji, Sandra Sukmaning (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
The application of green chemistry and environmental knowledge plays an important role in shaping individuals' awareness and actions toward environmental sustainability. By applying green chemistry and having good environmental knowledge, it can increase environmental awareness, so that it can increase environmental care behavior. Students who have good environmental knowledge have a more positive attitude toward the environment and tend to care more about the environment. Based on the background, the objectives of this research are: (1) to analyze the school community's perception of the concept of green chemistry and (2) to analyze the correlation between understanding green chemistry and the environment together with environmental care behavior. The research was conducted at SMA Kristen Harapan Denpasar using a random sampling technique with a sample size of 150 people. This research"™s independent variables are an understanding of green chemistry (X1) and an understanding of environmental concepts (X2). In contrast, the dependent variable is environmental care behavior (Y). Data analysis was done using descriptive statistics and Product Moment correlation analysis, followed by a t-test and F-test. Based on the research results it can be concluded that: (1) the level of perception of the school community towards green chemistry is 78% very good so it will be able to encourage better attitudes and behaviors towards the environment; (2) environmental care behavior of 11th grade students 58% in the good category, while 12th   grade students 60% in the good category, and there is a correlation between understanding of green chemistry, environmental concepts, and environmental care behavior collectively.